(Des)caminhos da teoria da função política de relações públicas : perspectivas antinômicas e sistêmicas da fundamentação na formação acadêmica - Tavares, Marcelo de Barros (2023)
The research theme is the theory of Public Relations, and its delimitation is centered on the organizational political function (SIMÕES, 1993; 1995; 2001; 2009), using the systemic approach (LUHMANN, 2016) and antinomic thinking (QUINTANA CABANAS, 2002 ) for understanding the academic training of/in Public Relations. Three macro objectives were defined: a) to analyze the theoretical foundation of Public Relations is represented in the curricular components of academic training; b) highlight the relevance [or not] of the theory of the political function (SIMÕES, 1993; 1995; 2001; 2009) in the curricular components of academic training; c) discuss how antinomic thinking (SIMÕES, 1993; QUINTANA CABANAS, 2002) can contribute to re-reading and updating the theory of the political function of Public Relations. The methodological procedures include bibliografphical and documentary research (MOREIRA, 2012), in-depth interviews (DUARTE, 2012) with a researcher and professors of reference in the area of teaching Public Relations. To analyze the findings, we resorted to content analysis (BARDIN, 2016) with coding, categorization and inferences. The reflection is divided into four stages: the place of theory, the predominant theoretical currents and approaches, the contributions of antinomic thought to the rereading and updating of the Theory of the Political Function. We found that the theories and/or theoretical currents/approaches of Publi Relations have a timid presence in academic training, and are predominantly concentrated in disciplines in the initial course of undergraduate courses. The results indicate that antinomic thinking is one of the methodological possibilities for teaching Public Relations through systemic and antinomian aspects in a reinterpretation of the organizational political function